Strategi Bertahan Hotel di Bali Saat Pandemi Covid-19 - Nuruddin .; Putu Eka Wirawan; Sri Pujiastuti; Ni Nyoman Sri Astuti (Pusat Kajian Bali Universitas Udayana, 2020)
The pandemic has paralyzed global tourism. In Bali, impacts of the pandemic on the tourism industry has been enormous. Almost all hotels stop operating, even if one opens, that opens itself to quarantine for Covid sufferers. This article examines the condition of hotels in Bali and the coping strategies adopted during the outbreak. This study uses a descriptive qualitative approach using in-depth interviews and literature studies on books, scientific journals, and online news. This research focuses on Four Seasons Resort Bali at Sayan, Alila Seminyak Bali, and Puri Saron Seminyak with reasons of star level representation and customer types. The results of this study indicate that the impact of the pandemic has resulted in almost zero hotels occupancy. They shared the same strategies that included to permanently and temporarily terminate employees, limit the use of hotel facilities, spend efficiency, sell non-room products online, and refuse booking refunds by changing visit schedules.